Differential Biofeedback Intervention In Moderating Inhibited Performance In Soccer - Soumendra, Saha; Srilekha, Saha; Mohd Zahir, Nurfarah Ezzaty; C, Debashis; K C, Prabal (EDP Sciences, 2016)
Performance excellence in soccer crucially depends on mental toughness or more specifically the aspect of emotional flexibility and hardiness of the player. Since indices of projective evaluations can reveal hidden emotional crises and internal conflicts, psychobiological evaluations could substantiate with the inner emotionality revealed to provide etiological information related to performance hindrances in soccer. Present study was carried out to identify the efficacy of skin conductance (Sc) biofeedback in regulation of sudomotor nerve activity (SNA) and of electromyography (EMG) biofeedback in regulation of peak torque and maximal voluntary contraction (MVC) in modification of performance catastrophe in soccer. All of them were assessed with autonomic measures (SNA and Sc amplitude); electromyography evaluation of emotionality and MVC revealed through EMG. Forty National-selection group soccer players of Malaysia were randomly categorized into four groups (Gr. A, N = 10, no-intervention control group); Gr. B (who received Sc biofeedback training); Gr. C (received EMG biofeedback intervention) and Gr. D (players who received combined training of Sc and EMG biofeedback intervention). Players of intervention groups received their respective trainings for 12 weeks (15 min.s /day for 3 days/ week). Postintervention analyses revealed marked improvement in the soccer players who received Sc and EMG biofeedback intervention, and the combined biofeedback training was evident as most efficient intervention technique in modulating emotionality as well as muscle potentiality. Analysis of variance and repeated measure of ANOVA were done to observe shared aetiology in the form of direct, inverse and supportive relationships between psychobiological and emotional indices related to performance crises in soccer. Comprehensive understanding of the confounding relationships between subjective feelings emotionality and corroborative psychobiological indices as predictor of high performance was achieved.